Which interest rate scenario is the worst one for a bank? Evidence from a tracking bank approach for German savings and cooperative banks - Christoph Memmel (Deutsche Bundesbank, 2008)
Interest income is the most important source of revenue for most of the banks. The aim of this paper is to assess the impact of different interest rate scenarios on the banks' interest income. As we do not know the interest rate sensitivity of real banks, we construct for each bank a portfolio with a similar composition of its assets and liabilities, called 'tracking bank'. We evaluate the effect of 260 historical interest rate shocks on the tracking banks of German savings banks and cooperative banks. It turns out that a sharp decrease in the steepness of the yield curve has the most negative impact on the banks' interest income. – – Der Zinsüberschuss ist für die meisten Banken die wichtigste Ertragsquelle. Stresstests in Bezug auf den Zinsüberschuss sind daher von wesentlicher Bedeutung. Die einzelnen Banken können solche Stresstests relativ einfach durchführen, weil ihnen die notwendigen Informationen (zukünftige Zahlungsströme und die Laufzeitstruktur der Forderungen und Verbindlichkeiten) vorliegen. Au?enstehende dagegen müssen die Laufzeitstruktur der Forderungen und Verbindlichkeiten auf Grundlage von Aktienkursänderungen oder Jahresabschlüssen schätzen.
Keywords: G12; G21; 330; Interest Rate Risk; Stress Testing